1969
DOI: 10.1104/pp.44.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Polyphenol Content, Activities and Isozymes of Polyphenol Oxidase and Peroxidase During Air-Curing in Three Tobacco Types

Abstract: Abstract. The change in polyphenol content in the primed leaves of burley, flue-cured, and Turkish tobaccos during air-curing was related to the activities and isozymes of polyphenol oxidase and peroxidase. The quantity of chlorogenic acid was rapidly reduced during the first week of curing. The decrease in rutin content during curing was less significant, especially when the concentration of chlorogenic acid was high in leaf tissues. This result was further confirmed by in vitro assays with partially purified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
1

Year Published

1970
1970
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 9 publications
3
18
1
Order By: Relevance
“…This contrasts with the data of Sheen (14,15), who reported that the zymograms were identical with either CA or DOPA as substrate and that the PPO patterns in a variety of tobacco tissues, including pith, were similar to those of peroxidase. His pith tissues also differed in containing as constitutive enzymes major activities of cathodic as well as anodic forms.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…This contrasts with the data of Sheen (14,15), who reported that the zymograms were identical with either CA or DOPA as substrate and that the PPO patterns in a variety of tobacco tissues, including pith, were similar to those of peroxidase. His pith tissues also differed in containing as constitutive enzymes major activities of cathodic as well as anodic forms.…”
Section: Discussioncontrasting
confidence: 55%
“…Both activities may involve isozymes and both are controlled, although in opposite ways, by IAA (1, 4, 10, 11). Re-cently, the pattern of isozymes of PPO' in tobacco tissues has been reported to be identical with or similar to that of peroxidase (14,15). In the present work, the possibility of a complex of enzymes catalyzing the oxidation of phenolic compounds and the hormonal control of the newly appearing isozymes has been explored in cultures of tobacco pith.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the enzyme assays, H 2 O 2 was used as the substrate for CAT (assay pH 7.0), indophenyl acetate for EST (assay pH 5.5), p-nitrophenyl phosphate for ACP (assay pH 5.2), orthodianisidine for POD (assay pH 6.0), o-catechol for PPO (assay pH 6.8), and diethylenetriamine pentaacetic acid, nitroblue tetrazolium and xanthine for SOD (pH 7.8). The isoenzyme profiles of CAT (Woodbury et al, 1971), EST (Brewbaker et al, 1968), ACP (Murray and Collier, 1977), POD (Sheen and Calvert, 1969), PPO (De Ascensao and Dubery, 2000) and SOD (Chen and Pan, 1996) were examined by native PAGE. Each experiment was replicated five times.…”
Section: Methodsmentioning
confidence: 99%
“…However, Weston (37) reported that peroxidase and polyphenoloxidase activities fluctuate similarly during growth and senescence of tobacco leaves. The discrepancy resulting from similar banding patterns for peroxidase and polyphenoloxidase isozymes after electrophoresis of tobacco leaf extracts (28) has since been resolved by Van Loon (34) using improved staining techniques. Changes in activity and isozyme composition of peroxidase (4) and of polyphenol oxidase (31) are subject to hormonal control.…”
mentioning
confidence: 99%